Effect of Movement Velocity during Resistance Training on Neuromuscular Performance - Pareja-Blanco, F.; Rodríguez-Rosell, D.; Sánchez-Medina, L.; Gorostiaga, E. M.; González-Badillo, J. J. (International Journal of Sports Medicine, 2014)
This study aimed to compare the effect on neuromuscular performance of 2 isoinertial resistance training programs that differed only in actual repetition velocity: maximal intended (MaxV) vs. half-maximal (HalfV) concentric velocity. 21 resistance-trained young men were randomly assigned to a MaxV (n=10) or HalfV (n=11) group and trained for 6 weeks using the full squat exercise. A complementary study (n=8) described the acute metabolic and mechanical response to the protocols used. MaxV training resulted in a likely more beneficial effect than HalfV on squat performance: maximum strength (ES: 0.94 vs. 0.54), velocity developed against all (ES: 1.76 vs. 0.88), light (ES: 1.76 vs. 0.75) and heavy (ES: 2.03 vs. 1.64) loads common to pre- and post-tests, and CMJ height (ES: 0.63 vs. 0.15). The effect on 20-m sprint was unclear, however. Both groups attained the greatest improvements in squat performance at their training velocities. Movement velocity seemed to be of greater importance than time under tension for inducing strength adaptations. Slightly higher metabolic stress (blood lactate and ammonia) and CMJ height loss were found for MaxV vs. HalfV, while metabolite levels were low to moderate for both conditions. MaxV may provide a superior stimulus for inducing adaptations directed towards improving athletic performance.
Keywords: full squat; velocity specificity; athletic performance; strength training; lactate; ammonia